Líquido folicular eqüino na produção in vitro de embriões bovinos - Pinto, Maicon Gaissler Lorena (2002)
Follicular fluid has been used for in vitro embryo production, although it offers the risk of disease transmission. The use of heterologous follicular fluid can be an alternative to avoid infection. The effect of equine follicular fluid (eFF) on embryonic development of bovine oocytes was evaluated. In Experiment I (EI), eFF was used as holding medium for immature bovine oocytes. In Experiment II (EII), maturation medium was supplemented with different concentrations of eFF. Oocytes for both experiments were obtained from ovaries collected at abattoir. For Experimennt I, 1228 Cumulus-oocyte complexes (COC´s) were distributed (13 replicate) on 3 treatments: T1, T2 and T3 and a control group (C). COC´s of the Control Group and T1 were matured (IVM) for 24 and 18h, respectively. COC´s of T2 and T3 were exposed, respectively, to eFF and bovine follicular fluid (bFF) for 6h at 30ºC, and matured for 18h. TCM 199 was used for IVM. On EII, 1045 COC`s were distributed (11 replicate) on 3 treatments: T1, T2 e T3 and a control group. TCM-199 with sodium pyruvate, rFSHh and Lhe was used as maturation medium. This basic medium was supplemented with 10% estrous mare serum for the control group, and 5, 10, 20% of eLF to treatments T1, T2 e T3, respectively. The COC´s were in vitro matured (IVM) for 24 hours. In vitro fertilization (IVF) and culture offers the same conditions for both experiments. IVF was performed in TALP-FERT medium. IVM and IVF were carried out in an incubator at 39ºC with 5% CO2 in air and saturated humidity. Zygotes were cultured in SOFaaci medium, under mineral oil in gasified plastic bags (Bag System). In experiment I, cleavage rate was lower in COC´s matured for 18h (T1, T2 and T3) than for 24h (Control). No differences were observed on blastocyst rates on D7 and hatching rates on D9. When oocytes were matured for 18h, blastocyst rates on D9 were higher on those COC´s exposed to Follicular Fluid. In experiment II, no differences were observed on cleavage and hatching rates. Blastocyst production on D7 and D9 were higher in T2 than T1 (P<0,05). Equine follicular fluid can be used for holding and maturing bovine oocytes producing similar rates of in vitro embryo development than that obtained for control group.